Rural and Remote Pharmacy Workforce Development Program - Sunderland, Vivian (WA Centre for Health Promotion Research, 2006)
Executive SummaryMany authors have commented upon the potential of pharmacies as a health promotion setting due to their ease of accessibility for the public, high level of use, and respected position of pharmacists.Research has demonstrated that pharmacist led health promotion can be successful in assisting people to make lifestyle changes around smoking, diet, and more specifically, lipid management. There is also preliminary evidence to suggest that pharmacists can provide physical activity and alcohol consumption recommendations to their customers.Presently pharmacists have mainly been involved in information provision and screening activities. This forms one component of a health promotion approach and particularly in rural regions, community pharmacies could be performing a greater role in community health promotion activities.A model was piloted in four rural pharmacies with each pharmacy provided with a small grant to cover community activities and in store health promotion advice provision. The primary researcher on the project offered consultation support to the pharmacies as well as conducting the literature review and project evaluation.Needs analyses were conducted in the pharmacies and feedback revealed a low level of interest in health behaviour topics although some customers mentioned an interest in receiving dietary advice. This reflected the lower use of the in-store component of the project with few customers utilising the free dietary checks. Falls prevention screening and diabetes screening were more popular.The pharmacies were able to organise and sponsor a wide range of health promotion community activities. These included workshops on health topics, physical activity programs, home reviews for falls prevention, and early years and school health promotion programs. These programs reached over 500 people across the four communities.The results showed the considerable potential for community pharmacies in rural areas to organise community health promotion activities. As well as the direct benefit to the people involved in these activities, having the pharmacy sponsor and organise the events contributes to changing the perceptions of the general public to realise the broad health expertise of pharmacies roles.Based on the literature review and findings of the project a model has been developed in the recommendations section to imbed health promotion within rural community pharmacies. Important aspects of this model are health promotion training for pharmacists and pharmacy assistants, provision of grant money support, consultation support from a health promotion worker and promotional material to advertise using the pharmacy for health promotion advice.